2012
DOI: 10.1177/1079063212447201
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of Suicide Attempts Among Incarcerated Sex Offenders

Abstract: Little is known about suicide attempts among sex offenders. This study examines the rates of nonfatal suicide attempts among a sample (N = 3,030) of incarcerated male sex offenders. Overall, the authors found that 14% of sex offenders in the study sample had made a suicide attempt at some point in their lives. Of those, 11% had reported a suicide attempt prior to incarceration, 0.5% had made a suicide attempt while incarcerated, and 2.5% made suicide attempts both prior to and during incarceration. Sex offende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
27
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 39 publications
3
27
0
Order By: Relevance
“…In the study of Jeglic et al from January 2013, 14% of all sexual offenders had a lifetime history of at least one suicide attempt. In this group no significant differences between pedophilic child molesters and rapists was observed [41]. The results of recent, large epidemiologic study in Danish population confirmed that suicide attempts were significantly more frequent in individuals with paraphilia than in general population [42].…”
Section: "Leading To the Conclusive Suicide"supporting
confidence: 51%
“…In the study of Jeglic et al from January 2013, 14% of all sexual offenders had a lifetime history of at least one suicide attempt. In this group no significant differences between pedophilic child molesters and rapists was observed [41]. The results of recent, large epidemiologic study in Danish population confirmed that suicide attempts were significantly more frequent in individuals with paraphilia than in general population [42].…”
Section: "Leading To the Conclusive Suicide"supporting
confidence: 51%
“…Given that most sex crimes are committed by people known to the victim (e.g., Colombino et al, 2009Colombino et al, , 2011Duwe et al, 2008;Greenfield, 1997;Smallbone & Wortley, 2000;Snyder, 2000), it is not surprising that evidence for these laws has been mixed, at best. At worst, evidence suggests that these laws may inadvertently serve to increase risk of recidivism (Hanson & Harris, 1998;Jeglic, Mercado, & Levenson, 2012;Jeglic, Spada, & Mercado, 2013;Lees & Tewksbury, 2006;Levenson & Cotter, 2005a, 2005bLevenson, D'Amora, & Hern, 2007;Mercado, Alvarez, & Levenson, 2008;Prescott & Rockoff, 2008;Zevitz, 2006Zevitz, , 2000.…”
mentioning
confidence: 97%
“…Three studies have addressed suicide risk in the broader population of sex offenders (Jeglic, Spada, & Mercado, 2013; Stinson & Gonsalves, 2014; Webb et al, 2012). Among these samples, predictors of suicidal behavior included mood, anxiety, and psychotic disorders as well as antisocial, borderline, and other cluster B personality disorders (Stinson & Gonsalves, 2014); history of child abuse or neglect, psychiatric history, and male victims (Jeglic et al, 2013); plus violent offenses and younger age (Webb et al, 2012).…”
mentioning
confidence: 99%